2020
DOI: 10.1111/crj.13300
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetics and altitude on lung function

Abstract: Objectives The aim of this work is to present a review on the impact of genetics and altitude on lung function from classic and recent studies. Data source A systematic search has been carried out in different databases of scientific studies, using keywords related to lung volumes, spirometry, altitude and genetics. Results The results of this work have been structured into three parts. First, the relationship between genes and lung function. Next, a review of the genetic predispositions related to respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 110 publications
0
2
0
1
Order By: Relevance
“…This such a exposure might triggered several mechanisms that have been associated with greater lung capacities. For instance, having greater FVC is probably linked to anatomical changes that have evolve from centuries of adaptation [ 6 , 33 35 ]. Some of these evolutionary anatomical adaptations (wider and deeper chest) confer these populations with larger lungs, which result in a greater capacity to accommodate more air.…”
Section: Discussionmentioning
confidence: 99%
“…This such a exposure might triggered several mechanisms that have been associated with greater lung capacities. For instance, having greater FVC is probably linked to anatomical changes that have evolve from centuries of adaptation [ 6 , 33 35 ]. Some of these evolutionary anatomical adaptations (wider and deeper chest) confer these populations with larger lungs, which result in a greater capacity to accommodate more air.…”
Section: Discussionmentioning
confidence: 99%
“…Such conjectures were verified to some extent in our LDSC results. Several observational studies pointed out that COPD was diagnosed when lung function parameters began to decrease, was characterized by airway limitation and was related to a higher risk of VTE events [ 12 , 50 , 51 ]. Additionally, a prospective population-based study indicated that airway obstruction can increase the risk of VTE events (provoked or unprovoked), and decreased FEV1 and FEV1/FVC, indices of obstructive ventilation dysfunction, were related to a higher risk of VTE events, especially PE [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A literatura é carente de artigos que descrevem as modificações de função pulmonar em populações semelhantes à analisada neste estudo. Existem relatos anteriores em populações que residem em ambientes de altitude elevada, considerando os efeitos temporários ou ainda a aclimatação a longo prazo (TALAMINOS-BARROSO et al, 2020). A adaptação vai ao encontro das mudanças nos mecanismos de controle respiratório (WEITZ; GARRUTO; CHIN, 2016), adaptações genéticas que são transferidas por gerações, como, desenvolvimento de maiores volumes pulmonares; alterações nos gradientes arterio-alveolares de oxigênio; e aumento do fluxo sanguíneo da artéria uterina durante a gravidez, sugerindo, portanto, uma melhor eficiência no transporte e consumo de oxigênio (TALAMINOS-BARROSO et al, 2020).…”
Section: Discussionunclassified